Clinical Outcomes of Elite Controllers, Viremic Controllers, and Long-Term Nonprogressors in the US Department of Defense HIV Natural History Study - Okulicz, Jason F.; Marconi, Vincent C.; Landrum, Michael L.; Wegner, Scott; Weintrob, Amy; Ganesan, Anuradha; Hale, Braden; Crum-Cianflone, Nancy; Delmar, Judith; Barthel, Vincent; Quinnan, Gerald; Agan, Brian K.; et al. (The Journal of infectious diseases, 2009)
Durable control of human immunodeficiency virus (HIV) replication and lack of disease progression in the absence of antiretroviral therapy were studied in a military cohort of 4586 subjects. We examined groups of elite controllers (ie, subjects with plasma HIV RNA levels of <50 copies/mL; prevalence, 0.55% [95% confidence interval CI, 0.35%–0.80%]), viremic controllers (ie, subjects with plasma HIV RNA levels of 50–2000 copies/mL; prevalence, 3.34% [95% CI, 2.83%–3.91%]), and subjects with a lack of disease progression (ie, long-term nonprogressors [LTNPs]) through 7 years of follow-up (LTNP7s; prevalence, 3.32% [95% CI, 2.70%–4.01%]) or 10 years of follow-up (LTNP10s; prevalence, 2.04% [95% CI, 1.52%–2.68%]). For elite and viremic controllers, spontaneous virologic control was established early and was typically observed when the initial viral load measurement was obtained within 1 year of estimated seroconversion. Elite controllers had favorable time to development of AIDS (P=.048), a CD4 cell count of 350 cells/μL (P=.009), and more-stable CD4 cell trends, compared with viremic controllers. LTNPs defined by 10-year versus 7-year criteria had a longer survival time (P=.001), even after adjustment for differing periods of invulnerability (P=.042). Definitions of controllers and LTNPs describe distinct populations whose differing clinical outcomes improve with the stringency of criteria, underscoring the need for comparability between study populations